Research on Halal Tourism in Indonesian Context: What Has Literature Told Us? - Muhamad Johari; Kasyfur Rahman (International Journal of Islamic and Social Sciences (ISOS), 2021)
As an emerging field of research, halal tourism has been increasingly grabbing researchers’ attention inthe academic realm. Nonetheless, due to its novel nature, scientific inquiry on this topic in Indonesiancontext seems to hither to be more theoretical rather than empirical. By exploring insights from scientificpublications on journals and proceedings dated from the last decade, we came up with a suggestion ofcalling for epitomes of more empirical evidence to develop body of knowledge on the topic. Current stateof the art of research on halal tourism in Indonesia still mostly circulates around the concept of halaltourism which is not clear cut though some researchers attempted to investigate people’s perceptions onthe concept and practices through surveys and group discussions. This paper suggests more researchdevoted to empirical findings which seek for evidence on the elements of halal tourisms that entail thepeople involved (guests and hosts), the destinations, and the travel management. All these elements arealso linked to the need of investigating local and national policies pertinent to the topic.